2016
DOI: 10.1080/10410236.2015.1048421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Character–Audience Similarity on the Perceived Effectiveness of Antismoking PSAs via Engagement

Abstract: This study assesses the impact of character-audience similarity, a core aspect of tailored communication, on evaluation of anti-smoking public service announcements (PSAs). Smoker and persuader characters are distinguished to explore their different roles in message effectiveness. Daily adult smokers (n = 1,160) were exposed to four video PSAs randomly selected from a larger pool. Similarity scores were determined from matching in demographic (age, gender, race) and motivational factors (quitting status) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 49 publications
0
24
0
9
Order By: Relevance
“…De forma congruente con este planteamiento, en el trabajo de Kim et al (2016), sobre mensajes narrativos centrados en la prevención del tabaquismo, se observó que la intensidad de la similitud entre el protagonista del mensaje y la audiencia (compartir 3 o más rasgos demográficos) era la condición para que se incrementara el enganche narrativo.…”
Section: Discusión Y Conclusionesunclassified
See 2 more Smart Citations
“…De forma congruente con este planteamiento, en el trabajo de Kim et al (2016), sobre mensajes narrativos centrados en la prevención del tabaquismo, se observó que la intensidad de la similitud entre el protagonista del mensaje y la audiencia (compartir 3 o más rasgos demográficos) era la condición para que se incrementara el enganche narrativo.…”
Section: Discusión Y Conclusionesunclassified
“…El primer elemento sobre el que queremos centrar la atención en este trabajo es la similitud de la audiencia con el protagonista del mensaje, dado que la evidencia empírica no es concluyente (Chen, Bell, & Taylor, 2016;Cohen, Weimann-Saks, & Mazor-Tregerman, 2017;de Graaf, 2014;de Graaf et al, 2016;Hoeken et al, 2016;Kim, Shi, & Cappella, 2016;Tukachinsky, 2014). La similitud describe un proceso a través del cual la persona que se expone a un mensaje narrativo evalúa hasta qué punto comparte ciertos rasgos con su protagonista.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…For instance, Tukachinsky's review (2014) only took into account works that had manipulated similarity in demographic variables such as sex, age and ethnicity. Secondly, this review does not include more recent works that have found an effect of similarity on identification and attitudes (Chen et al, 2016;Hoeken et al, 2016;Kim et al, 2016). Thirdly, it has been found that sometimes similarity has no effect on identification, but it does have an indirect effect on attitudes (de Graaf, 2014;Igartua & Fiuza, 2017).…”
Section: Narrative Persuasion: the Impact Of Character Similarity On mentioning
confidence: 99%
“…The first element of analysis in this work is the similarity of the audience with the protagonist of the message, given that evidence is not conclusive in this area (Chen, Bell, & Taylor, 2016;Cohen, Weimann-Saks & Mazor-Tregerman, 2017;de Graaf, 2014;de Graaf et al, 2016;Hoeken et al, 2016;Kim, Shi, & Cappella, 2016;Tukachinsky, 2014). Similarity describes a process through which the person who is exposed to a narrative message assesses to what extent he or she shares certain traits with the protagonist.…”
Section: Narrative Persuasion: the Impact Of Character Similarity On mentioning
confidence: 99%